Effects of Replacement of Dietary Fishmeal by Cottonseed Protein Concentrate on Growth Performance, Liver Health, and Intestinal Histology of Largemouth Bass (Micropterus salmoides) - Liu, Yulong; Lu, Qisheng; Xi, Longwei; Gong, Yulong; Su, Jingzhi; Han, Dong; Zhang, Zhimin; Liu, Haokun; Jin, Junyan; Yang, Yunxia; Zhu, Xiaoming; Xie, Shouqi (Frontiers in Physiology, 2021)
An 8-week feeding trial was conducted to explore the effects of replacement of dietary fishmeal by cottonseed protein concentrate (CPC) on growth performance, liver health, and intestine histology of largemouth bass. Four isoproteic and isolipidic diets were formulated to include 0, 111, 222, and 333 g/kg of CPC, corresponding to replace 0% (D1), 25% (D2), 50% (D3), and 75% (D4) of fishmeal. Two hundred and forty largemouth bass (15.11 ± 0.02 g) were randomly divided into four groups with three replicates per group. During the experiment, fish were fed to apparent satiation twice daily. Results indicated that CPC could replace up to 50% fishmeal in a diet for largemouth bass without significant adverse effects on growth performance. However, weight gain rate (WGR), specific growth rate (SGR), feed efficiency (FE), and condition factor (K) of the largemouth bass were significantly decreased when 75% of dietary fishmeal that was replaced by CPC. The whole body lipid content was increased with the increasing of dietary CPC levels. Oil red O staining results indicated that fish fed the D4 diet showed an aggravated fat deposition in the liver. Hepatocytes exhibited serious degeneration, volume shrinkage, and inflammatory cells infiltration in the D4 group. Intestinal villi appeared shorter and sparse with severe epithelial damage in the D4 group. The transcription levels of anti-inflammatory cytokines, such as transforming growth factor β (tgf-β), interleukin 10 (il-10), and interleukin 11 β (il-11β), were downregulated in the D4 group. The lipid metabolism-related genes carnitine palmitoyl transferase 1 (cpt1), peroxisome proliferator-activated receptor α (pparα), and target of rapamycin (TOR) pathway were also significantly downregulated in the D4 group. It was concluded that suitable replacement of fishmeal by less than 222 g CPC/kg diet had a positive effect on growth performance of fish, but an excessive substitution of 75% fishmeal by CPC would lead to the suppressed growth, liver inflammation, and intestinal damage of largemouth bass.